Chiral susceptibility in (2+1)-flavor QCD - Braun, Jens; Fu, Wei-jie; Pawlowski, Jan M.; Rennecke, Fabian; Rosenblüh, Daniel; Yin, Shi (Physical review, 2020)
We calculate chiral susceptibilities in (2+1)-flavor QCD for different masses of the light quarks using the functional renormalization group (fRG) approach to first principles QCD. We follow the evolution of the chiral susceptibilities with decreasing masses as obtained from both the light-quark and the reduced quark condensate. The latter compares very well with recent results from the HotQCD Collaboration for pion masses mπ≳100 MeV. For smaller pion masses, fRG and lattice results are still consistent. In particular, the estimates for the chiral critical temperature are in very good agreement. We close by discussing different extrapolations to the chiral limit.
Gesehen am 14.10.2022